Enzymatic Browning in Wheat Kernels Produces Symptom of Black Point Caused by Bipolaris sorokiniana - Li, Qiaoyun; Xu, Kaige; Wang, Siyu; Li, Mengyu; Jiang, Yumei; Liang, Xiaolong; Niu, Jishan; Wang, Chenyang (Frontiers in Microbiology, 2020)
To understand the blackening mechanism in black point diseased kernels, ultraviolet-visible light (UV-Vis) and Fourier-transform infrared (FT-IR) absorbance spectra of extracts made from the blackening parts of black point-affected (BP) kernels and the analogous part of black point-free (BPF) kernels were measured using susceptible wheat genotypes ‘PZSCL6’ inoculated with Bipolaris sorokiniana (the dominant pathogen causing this disease). In addition, metabolite differences between BP and BPF kernels were identified by a method that combines gas chromatography-mass spectrometry and liquid chromatography-high resolution mass spectrometry. Successively, symptoms of black point were produced in vitro. The results showed (i) the spectroscopic properties of the extracts from BP and BPF kernels were very similar, with an absorption peak at 235 nm and a small shoulder at 280-300 nm in both UV-Vis spectra and shared vibrations at 3400-3300 cm-1, 2925 cm-1 and 2852 cm-1, 1512 cm-1 and 1463 cm-1, 1709 cm-1, 1220 cm-1, 600-860 cm-1 in FT-IR spectra that are consistent with similar bonding characteristics. In contrast, spectroscopic properties of extracts from wheat kernels were different from those of synthetic melanin and extracellular and intracellular melanin produced by B. sorokiniana. (ii) Levels of 156 metabolites in BP kernels were different from those in BPF kernels. Amongst those 156 metabolites, levels of phenolic acids (ferulic acid and p-coumaric acid), 11 phenolamides compounds, and four benzoxazinone derivatives were significantly higher in BP kernels than in BPF kernels. (iii) Symptom of black point could be produced in vitro in wheat kernels with supplement of phenol substrate (catechol) and H2O2. This result proved that blackening substance causing symptom of black point was produced by enzymatic browning in wheat kernels instead of by B. sorokiniana.